Distribuição da literatura científica brasileira: estudo bibliométrico - Gomes, Samuel (1977)
Bibliometrics - "quantitative treatment of the properties and behaviour of recorded information" - has been widely applied in the last fewn years. Among the bibliometric laws, Bradford’s law, also called "laws of dispersion of literature" - stands out as one of the most widely known and generalizable. Application of the bibliometric laws has been restricted, nevertheles, mainly to the literatures of the basic sciences and techonology, while the human sciences are less considered for that kind of analysis. The reason for this limitation is the assumption that the literatures of the human sciences, including the social sciences, are mnore dispersed and therefore their complete recording is more difficult. Application of the Bradford’s law to the Brazilian literature in several scientific areas in the context of the present work did not show, as one could expect, greater dispersion nor irregularity in the human sciences than in the other sciences. The patterns of behaviour are quite similar. The most remnarkable irregularities observed were: wolly linear, zipfian behaviour (as in Law, Geology 17); excessive dispersion in the last zone or zones (all the literatures). The irregularities noted are probablt due to the stage of development (fast but still little organized) of science in Brazil or at least of the areas studied. The suggestion for obtaining a better control od the more dispersed literature is the creation od periodical banks for groups of scientific areas such as: "basic sciences", "techonology", "human sciences".